2014
DOI: 10.5539/jas.v6n5p120
|View full text |Cite
|
Sign up to set email alerts
|

Using DSSAT-CENTURY Model to Simulate Soil Organic Carbon Dynamics Under a Low-Input Maize Cropping System

Abstract: Decline in Soil Organic Carbon (SOC) below the critical levels is one of the major indicators of soil fertility depletion in Sub-Saharan Africa (SSA), with the main causes being poor management practices coupled with low input use. Measures for monitoring long-term impacts of management on SOC dynamics and its restoration can be critical in enhancing sustainable soil productivity. Crop models have proved to be good tools for understanding the influence of management options on soil and crop productivity. The D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…We tested this hypothesis using the CENTURY module included in the Decision Support System for Agrotechnology Transfer (DSSAT) software (Hoogenboom et al, 2015; Porter et al, 2010) to simulate long‐term SOC dynamics in two long‐term experiments from the midwest United States and southern Brazil. The DSSAT‐CENTURY model has been used to simulate SOC dynamics in both low‐ and high‐yield agroecosystems (Gijsman, Hoogenboom, Parton, & Kerridge, 2002; Li, Yang, Drury, & Hoogenboom, 2015; Liu et al, 2017; Musinguzi et al, 2014). The experiments included in our study tested different soil tillage systems, nitrogen (N) sources and crop rotation with frequent plant and soil sampling.…”
Section: Introductionmentioning
confidence: 99%
“…We tested this hypothesis using the CENTURY module included in the Decision Support System for Agrotechnology Transfer (DSSAT) software (Hoogenboom et al, 2015; Porter et al, 2010) to simulate long‐term SOC dynamics in two long‐term experiments from the midwest United States and southern Brazil. The DSSAT‐CENTURY model has been used to simulate SOC dynamics in both low‐ and high‐yield agroecosystems (Gijsman, Hoogenboom, Parton, & Kerridge, 2002; Li, Yang, Drury, & Hoogenboom, 2015; Liu et al, 2017; Musinguzi et al, 2014). The experiments included in our study tested different soil tillage systems, nitrogen (N) sources and crop rotation with frequent plant and soil sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcing farmers' knowledge with simple quantifiable scientific indicators is therefore important. The coherent ratings in low-fertility fields in both techniques can be instrumental for easily guiding generalized fertilizer application and fertility restoration strategies (Bekunda et al, 2010;Musinguzi et al, 2014). The findings with FFE technique also suggest that the threshold value of SOC could be lower than 1.2 % from the maize yield predictions.…”
Section: Soil Productivity Rated Using Farmers' Field Experiences Andmentioning
confidence: 64%
“…The DSSAT model simulates soil organic matter (SOM) decomposition processes as a potential major source of nutrients for low input farming systems. SOM can increase cation exchange capacity, moisture storage, and mineralizable nutrient levels, as well as improve soil structure and aggregate stability (Musinguzi et al 2014). Therefore, an understanding of the dynamics of SOM can be used to help develop best management practices for sustainable soil productivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yang et al (2013) simulated the effects of long-term N fertilization on maize yield and soil C and N dynamics in northeast China, and concluded that the DSSAT model with the CENTURY-based soil module can simulate soil N dynamics and predict long-term soil organic carbon (SOC) sequestration well. Musinguzi et al (2014) used the DSSAT-CENTURY model to simulate SOC dynamics in a low-input maize cropping system, and found that the model was a potentially useful tool for predicting SOC dynamics in low-input systems. However, limited information is available about the use of the DSSAT model to study impacts of N fertilizer application on crop growth in the wheat-maize rotation system in the North China Plain region.…”
Section: Introductionmentioning
confidence: 99%